Child abuse in children living with special guardians, a service evaluation of child protection medical examinations. Issue 1 (2nd July 2021) - Garstang, Joanna; Hallett, Nutmeg; Cropp, Gabrielle; Kenyon-Blair, Davina; Morgans, Clare; Taylor, Julie
Abstract : Objective: To determine difference in frequency of referral for child protection medical examination (CPME) in children subject to special guardianship order (SGO), subject to child protection plan (CPP) or neither. Design: Service evaluation analysing data from CPME reports. Setting: Acute and community healthcare providers in Birmingham UK, during 2018. Patients: All children aged 0–18 years requiring CPME. Main outcome measures: Details were obtained from CPME reports on: age, SGO status, CPP status, reason for CPME, injuries sustained, presence of non-accidental injury. Population data were obtained from the local children's safeguarding board and national statistics. Results: Reports were available for 292/298 (98%) CPME, relating to 288 children. 5 children were subject to SGO, 39 were subject to CPP, none subject to both. Non-accidental injury was substantiated in 189/288 (66%). The child population was 288 000. 1665 children were subject to CPP and approximately 750 subject to SGO. The relative risk (RR) for children subject to SGO requiring a CPME compared with children not subject to SGO or CPP is 7.86, p<0.0001 with 95% CI (3.26 to 19.02). The RR for children subject to a CPP requiring CPME compared with children not subject to SGO or CPP is 27.65, p<0.0001 with 95% CI (19.78 to 38.63). Conclusions: This is a small study and findings need interpreting cautiously. Children subject to SGO may potentially be at higher risk of abuse than the general population despite living with carers who have passed social care parenting assessments. There is no register of children subject to SGO so professionals may be unable to offer families additional support. SGO families should be offered enhanced support and monitoring routinely. Children subject to CPP are not being adequately protected from further abuse.